Integrating form errors and local surface deformations into tolerance analysis based on skin model shapes and a boundary element method. (November 2018) - Liu, Jianhua; Zhang, Zhiqiang; Ding, Xiaoyu; Shao, Nan
Abstract: Tolerance analysis aims to ensure the performance of mechanical products. However, traditional analysis methods largely ignore the effects of form errors and local surface deformations, which are inevitably introduced during manufacturing and assembly phases. Therefore, this paper proposes a novel tolerance analysis framework integrating form errors and local surface deformations based on skin model shapes and a Boundary Element Method (BEM) for rectangular surfaces. First, it introduces a method for modeling skin model shapes considering form errors for rectangular surfaces. Next, it presents the calculation of local surface deformations based on the Conjugate Gradient-Fast Fourier Transform (CG-FFT) method, a classic BEM method for solving contact problems. Together, these can be used to obtain the relative positioning of mating surfaces considering the effects of form errors and local surface deformations. Case studies revealed the considerable effects of form errors and local surface deformations on assembly deviations, and demonstrated the efficiency of the proposed tolerance analysis process. Because the proposed tolerance analysis framework couples geometric deviations introduced during the manufacturing phase with mechanical deformations introduced during the assembly phase, it is expected to help control the geometric deviations of mechanical assemblies more accurately and also ensure product performance. Highlights: Form errors and local surface deformations are integrated in tolerance analysis. Skin model shapes with position, orientation, and form errors are generated. Local surface deformations are calculated using CG-FFT method.